Taxonomy of Sisyrinchium sect. Cephalanthum (Iridaceae: Iridoideae) in Southern Brazil - Inácio, Camila Dellanhese; Eggers, Lilian (Phytotaxa, 2020)
Here we present a first contribution to the taxonomic revision of Sisyrinchium (Iridaceae: Iridoideae) for Southern Brazil. Sisyrinchium sect. Cephalanthum is one of the six sections in which the Brazilian species of the genus are classified, and the second largest in number of taxa. This monograph presents the taxonomic treatment of 22 taxa characterized by a unique set of morphological and molecular features, assigned to the section by phylogenetic studies, as well as the unplaced S. elegantulum, which is included here due to morphological similarity. A new status and a new synonym are proposed, and nine lectotypes and one neotype are designated. An identification key is provided, and species are described, accompanied by botanical illustrations, pictures, and distribution maps. In addition, geographical distribution, habitat, phenology, notes, and examined specimens are presented. Species of the section are mainly distributed in the South American biogeographic dominions of Chacoan and Parana.